Need to Seed? Ecological, Genetic, and Evolutionary Keys to Seed-Based Wetland Restoration - Kettenring, Karin M.; Tarsa, Emily E. (Frontiers in Environmental Science, 2020)
As we approach the Decade of Ecosystem Restoration (2021–2030), there is renewed focus on improving wetland restoration practices to reestablish the habitat and climate mitigation functions and services that wetlands provide. A first step in restoring these functions and services is to reestablish the native vegetation structure and composition through strategic seed-based approaches. These approaches should be driven by ecological, genetic, and evolutionary principles, along with consideration for economics, logistics, and other social constraints. Effective seed-based approaches must consider the chosen species, seed sourcing, dormancy break and germination requirements, seed enhancement technologies, potential invaders, seeding densities, and long-term monitoring. Choice of species should reflect historical plant communities and future environmental conditions, species that support functional goals including invasion resistance, and seed availability constraints. Furthermore, seeds should be sourced to ensure ample genetic diversity to support multifunctionality and evolutionary capacity while also considering the broad natural dispersal of many wetland species. The decision to collect wild seeds or purchase seeds will also impact species choice and genetic diversity, which can have cascading effects for functional goals. To ensure seedling establishment, seed dormancy should be addressed through dormancy breaking treatments and the potentially narrow germination requirements of some species will require targeted sowing timing and location to align with safe sites. Other seed enhancements such as priming and coatings are poorly developed for wetland restoration and their potential for improving establishment is unknown. Because wetlands are highly invasion prone, potential invaders and their legacies should be addressed. Seeding densities should strike a balance between outcompeting invaders and preserving valuable seed resources. Invader control and long-term monitoring is key to improving revegetation and restoration. Here, we review scientific advances to improve revegetation outcomes, and provide methods and recommendations to help achieve the desired goals. Gaps in knowledge about seed-based wetland restoration currently exist, however, and untested practices will certainly increase risks in future efforts. These efforts can be used to better understand the ecological, genetic, and evolutionary processes related to wetland seeds, which will bring us one step closer to seed-based restoration of functions and services needed for human and ecological communities.